Fatores contingenciais e ciclo de vida organizacional: um estudo de caso em uma pequena indústria de organomineral - Gafuri, Raquel Adriana Pin (2016)
The search for better ways to manage business became more evident after the Industrial Revolution, and was a management accounting that boosted research in order to foster information to guide decision-making and optimize results. With the advancement of research has contacted that there is no single way to manage for all types of organizations and so did the Contingency theory that considers the company an open system subject to variables such as external environment influences, technology, structure, strategy and organizational size. Over time, many changes take place in a company and with them the problems arise, requiring new forms of management. At these phase changes, are called stages of organizational life cycle. Thus, through a case study we sought to identify how the contingent factors are perceived in the current phase of the life cycle of a small organic-industry. An exploratory research with data collection via document analysis, direct observation, informal conversations and structured interview questionnaire, you can see, on the perception of respondents that the organization is in the growth phase in its organizational life cycle. As for the contingency factors, the environment in which the company operates is stable, diversified and dominated by a few companies; the structure as it can be classified as organic more; the technology factor is considered as standard, but aggregate the information needs improvement; on strategic priorities, the search for customer quality and innovation of the product and service are more evident than the end product. Because it is a single case study, the impossibility of generalizing the results achieved limiting the intervention is considered. The study as a contribution the fact empirically demonstrate the contingent factors in a company. Aims to stimulate the search for knowledge about the interrelation between the stages of the life cycle and the contingency factors.